2008
DOI: 10.1080/03640210802138755
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Pitch Accents in Online Comprehension: H* vs. L+H*

Abstract: Although the presence or absence of a pitch accent clearly can play an important role in signaling the discourse and information structure of an utterance, whether the form of an accent determines the type of information it conveys is more controversial. We used an eye-tracking paradigm to investigate whether H * , which has been argued to signal new information, evokes different eye fixations than L+H * , which has been argued to signal the presence of contrast. Our results demonstrate that although listeners… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
124
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(146 citation statements)
references
References 28 publications
15
124
2
1
Order By: Relevance
“…For example, differences in semantic focus are associated with differences in pitch range in a wide variety of languages [e.g., Cooper et al, 1985;Xu and Xu, 2005;Féry and Kügler, 2008;Genzel and Kügler, 2010]. Furthermore, listeners have been shown to interpret pitch range differences in terms of distinct patterns of semantic reference or pragmatic intent [Hadding-Koch and Studdert-Kennedy, 1964;Studdert-Kennedy and Hadding-Koch, 1973;Nash and Mulac, 1980;Bartels and Kingston, 1994;Niebuhr, 2007b;Watson et al, 2008]. Evidence for pitch range as the phonetic basis of meaning contrasts comes from semantic judgment tasks, production studies, and eyetracking studies [Ward and Hirschberg, 1985;Hirschberg and Ward, 1992;Bartels and Kingston, 1994;Gussenhoven and Rietveld, 2000;Calhoun, 2006;Weber et al, 2006;Féry and Kügler, 2008;Watson et al, 2008].…”
Section: Pitch Range Variation In English Tonal Contrastsmentioning
confidence: 99%
“…For example, differences in semantic focus are associated with differences in pitch range in a wide variety of languages [e.g., Cooper et al, 1985;Xu and Xu, 2005;Féry and Kügler, 2008;Genzel and Kügler, 2010]. Furthermore, listeners have been shown to interpret pitch range differences in terms of distinct patterns of semantic reference or pragmatic intent [Hadding-Koch and Studdert-Kennedy, 1964;Studdert-Kennedy and Hadding-Koch, 1973;Nash and Mulac, 1980;Bartels and Kingston, 1994;Niebuhr, 2007b;Watson et al, 2008]. Evidence for pitch range as the phonetic basis of meaning contrasts comes from semantic judgment tasks, production studies, and eyetracking studies [Ward and Hirschberg, 1985;Hirschberg and Ward, 1992;Bartels and Kingston, 1994;Gussenhoven and Rietveld, 2000;Calhoun, 2006;Weber et al, 2006;Féry and Kügler, 2008;Watson et al, 2008].…”
Section: Pitch Range Variation In English Tonal Contrastsmentioning
confidence: 99%
“…, 'RED violin') results in more fixations to an object of the same type as in the first instruction (e.g., 'violin') than to another red object (e.g., 'vase') displayed on the screen (Ito & Speer, 2008;Weber, Braun, & Crocker, 2006). Interestingly, listeners not only make use of pitch accent distribution (i.e., accentuation of referent or adjective) but also appear to be sensitive to pitch accent type: A contrastive pitch accent such as L + H* (high pitch on the stressed syllable preceded by a low tone which results in a steep rise to the peak) creates a strong bias towards contrastive referents, while H* signals both new and contrastive referents (Watson, Tanenhaus, & Gunlogson, 2008). Taken together, these results show that listeners use intonational contrast marking and the situational context (e.g.…”
mentioning
confidence: 99%
“…Braun & Tagliapietra, 2010;Calhoun, 2012;Krahmer & Swerts, 2001;Watson et al, 2008). For example, Ladd and Morton (1997) showed that listeners could assign degree of emphasis in a gradient manner consistent with a continuum of F0 excursions that varied in the peak height between two rise-fall contours, which respectively represented a canonical H* accent and a L+H* accent.…”
Section: Contrastive Prosody: Categorical Distinction Despite Variantmentioning
confidence: 95%